2019
DOI: 10.1002/ajmg.a.61459
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the 2017 diagnostic criteria for hEDS by the Toronto GoodHope Ehlers–Danlos syndrome clinic: A retrospective review

Abstract: The new 2017 diagnostic criteria for hypermobile Ehlers–Danlos Syndrome (hEDS) provide a framework for diagnosing hEDS but are more stringent than the previous Villefranche criteria. Our clinical experience at the GoodHope EDS clinic was that the 2017 criteria left many highly symptomatic patients without a diagnosis of hEDS. We conducted a retrospective cohort study to confirm our clinic experience and assess the accuracy of the 2017 diagnostic criteria for hEDS in patients who had a previous hEDS diagnosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…The degree of hypermobility (according to the Beighton scale) showed no relation to the degree of associated symptoms, which suggests that hypermobility is only a subsymptom; this has recently been confirmed by McGillis et al 15 Most of the key observed symptoms were somewhat more common in the hEDS group than the HSD group, although only fatigue and a diagnosis of ADHD were significantly more common; this is what we expected because these are criteriabased diagnoses, and more criteria are required for a hEDS diagnosis than for HSD. However, none of these associated symptoms are included in the hEDS or HSD criteria.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The degree of hypermobility (according to the Beighton scale) showed no relation to the degree of associated symptoms, which suggests that hypermobility is only a subsymptom; this has recently been confirmed by McGillis et al 15 Most of the key observed symptoms were somewhat more common in the hEDS group than the HSD group, although only fatigue and a diagnosis of ADHD were significantly more common; this is what we expected because these are criteriabased diagnoses, and more criteria are required for a hEDS diagnosis than for HSD. However, none of these associated symptoms are included in the hEDS or HSD criteria.…”
Section: Discussionmentioning
confidence: 77%
“…Neuropsychiatric Disease and Treatment 2021:17 380 our retrospective study can be relevant to future clinical work because, for example, one study found a similar frequency of comorbidities of hEDS (such as gastrointestinal dysfunction and psychological comorbidities) in those patients who met the new criteria and those who did not. 15…”
Section: Dovepressmentioning
confidence: 99%
“…Patients who do not meet enough criteria for hEDS are often diagnosed with HSD or may lose a previous diagnosis after the new 2017 criteria, despite hEDS/HSD being indistinguishable in regard to severity of symptoms. 95,96 Because of this, the 2017 diagnostic criteria have received much criticism. 95…”
Section: Col1a1mentioning
confidence: 99%
“…It is essential that physicians recognize signs of hypermobility and ligament laxity early on and make necessary recommendations and referrals to prevent chronic joint damage and complications of the disease. Patients who do not meet enough criteria for hEDS are often diagnosed with HSD or may lose a previous diagnosis after the new 2017 criteria, despite hEDS/HSD being indistinguishable in regard to severity of symptoms 95,96 . Because of this, the 2017 diagnostic criteria have received much criticism 95 …”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…That may not matter, because the new criteria have been criticized for being too restrictive. McGillis et al 18 reported that the 2017 diagnostic criteria leave many highly symptomatic patients without a diagnosis. Further, the newest diagnostic criteria have not been validated and, thus, require refi nement to improve their diagnostic accuracy.…”
Section: Date Of Her Diagnosis Importantmentioning
confidence: 99%